The Impact of Pedagogic Competence and Motivation on the Performance of Transformational Teachers in Pidie Regency - Ismarni, Beri; Rasyid, Suparta; Niswanto, Niswanto (Asian Journal of Applied Education (AJAE), 2025)
Teachers who already have a Transformational Teacher certificate must have high pedagogic competence and motivation in order to become a model roel in the progress and renewal of educational achievements. This study aims to analyze the level of influence of pedagogic competence and motivation possessed by Transformational Teachers in Pidie Regency. Data collection was carried out by distributing questionnaires directly to all Penggerak teachers in Pidie district with a total population of 319 people, sampling using the Slovin formula with a significant level of 5% so that a sample of 177 people was obtained. The methods used in this study are quantitative and data analysis using the SEM PLS software model. The results of the study were obtained by the Pedagogic Competence pathway on the Performance of Transformational Teachers of 0.344 while the Motivation of Transformational Teachers on the Performance of Transformational Teachers was 0.452. This finding has important implications for teachers in carrying out their duties for the advancement of education. Therefore, further research is needed to explore other factors that affect low teacher performance.